Expression of Extracellular Vesicle PIWI-Interacting RNAs Throughout hiPSC-Cardiomyocyte Differentiation - Louro, Ana F.; Virgolini, Nikolaus; Paiva, Marta A.; Isidro, Inês A.; Alves, Paula M.; Gomes-Alves, Patrícia; Serra, Margarida (Frontiers in Physiology, 2022)
Extracellular Vesicles (EV) play a critical role in the regulation of regenerative processes in wounded tissues by mediating cell-to-cell communication. Multiple RNA species have been identified in EV, although their function still lacks understanding. We previously characterized the miRNA content of EV secreted over hiPSC-cardiomyocyte differentiation and found a distinct miRNA expression in hiPSC-EV driving its in vitro bioactivity. In this work, we investigated the piRNA profiles of EV derived from key stages of the hiPSC-CM differentiation and maturation, i.e., from hiPSC (hiPSC-EV), cardiac progenitors (CPC-EV), immature (CMi-EV), and mature (CMm-EV) cardiomyocytes, demonstrating that EV-piRNA expression differs greatly from the miRNA profiles we previously identified. Only four piRNA were significantly deregulated in EV, one in hiPSC-EV, and three in CPC-EV, as determined by differential expression analysis on small RNA-seq data. Our results provide a valuable source of information for further studies aiming at defining the role of piRNA in the bioactivity and therapeutic potential of EV.